Human diseases caused by germline and somatic abnormalities in microRNA and microRNA‐related genes. (February 2014) - Kawahara, Yukio
Abstract The human genome harbors approximately 2000 genes that encode microRNAs (miRNAs), small non‐coding RNAs of approximately 20–22 nt that mediate post‐transcriptional gene silencing. MiRNAs are generated from long transcripts through stepwise processing by the Drosha/DGCR8, Exportin‐5/RanGTP and Dicer/TRBP complexes. Given that the expression of each individual miRNA is tightly regulated, the altered expression of certain miRNAs plays a pivotal role in human diseases. For instance, germline and somatic mutations in the genes encoding the miRNA processing machinery have been reported in different cancers. Furthermore, certain miRNA genes are encoded within regions that are deleted or duplicated in individuals with chromosomal abnormalities, and the fact that the knockout of these miRNAs in animal models results in lethality or the abnormal development of certain tissues indicates that these miRNA genes contribute to the disease phenotypes. It has also been reported that mutations in miRNA genes or in miRNA‐binding sites, which result in the impairment of tight regulation of target mRNA expression, cause human genetic diseases, although these cases are rare. This is in contrast to the aberrant expression of certain miRNAs that results from the impairment of transcriptional or post‐transcriptional regulation, which has been reported frequently in various human diseases. The present review focuses on human diseases caused by mutations in genes encoding miRNAs and the miRNA processing machinery as well as in miRNA‐binding sites. Furthermore, human diseases caused by chromosomal abnormalities that involve the deletion or duplication of regions harboring genes that encode miRNAs or the miRNA processing machinery are also introduced.